1992
DOI: 10.1002/1097-0142(19920701)70:1<45::aid-cncr2820700108>3.0.co;2-7
|View full text |Cite
|
Sign up to set email alerts
|

Tumor encapsulation in hepatocellular carcinoma. A pathologic study of 189 cases

Abstract: One hundred eighty‐nine surgically resected hepatocellular carcinomas (HCC) were analyzed to study tumor encapsulation and the pathologic features that might account for the better prognosis in relation to it, and to examine the prognostic and pathobiologic significance of capsular thickness. Tumor encapsulation was found in 72 (46.8%) of the 154 cases with adequate histologic sections of the tumor‐nontumor junctions. Encapsulated tumors showed a much lower incidence of direct liver invasion (P < 0.0001), tumo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
100
1

Year Published

1994
1994
2007
2007

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 170 publications
(111 citation statements)
references
References 13 publications
10
100
1
Order By: Relevance
“…34 Conversely, MMP2, MT1-MMP, and TIMP2 mRNA levels in nontumor livers were not correlated with the presence or absence of capsule (not shown), consistent with the previous demonstration that tumor encapsulation was independent of the cirrhotic process. 34 MMP2 activities in HCCs and matching nontumor livers were correlated. In addition, MMP2 activity was higher in tumors arising in cirrhotic livers than in those arising in noncirrhotic livers, and it was associated with the stage of fibrosis.…”
Section: Discussionsupporting
confidence: 90%
“…34 Conversely, MMP2, MT1-MMP, and TIMP2 mRNA levels in nontumor livers were not correlated with the presence or absence of capsule (not shown), consistent with the previous demonstration that tumor encapsulation was independent of the cirrhotic process. 34 MMP2 activities in HCCs and matching nontumor livers were correlated. In addition, MMP2 activity was higher in tumors arising in cirrhotic livers than in those arising in noncirrhotic livers, and it was associated with the stage of fibrosis.…”
Section: Discussionsupporting
confidence: 90%
“…These groups of patients usually have a poor disease outcome, which is in agreement with our current observation. 43 In conclusion, the high expression of CYP2E1 in adjacent nontumor tissue may play an important role in HCC carcinogenesis through metabolizing procarcinogens and generating reactive oxygen species. The low level of CYP2E1 in tumor tissue, which was found in patients with more aggressive type of tumor and poor prognosis, may allow the rapid proliferation of the tumor cells by escaping the cytotoxicity generated by CYP2E1.…”
Section: Cyp2e1 Protein Expression and Clinicopathological Features Omentioning
confidence: 97%
“…Encapsulated HCCs appear to be less aggressively invasive than tumours without this feature. 129 Vascular invasion is valued as an early indicator of the aggressiveness of a tumour (for example, its metastatic potential or the likelihood of rapid recurrence following treatment). 130 Rates of vascular invasion are significantly lower in tumours that are small, 131 histologically well differentiated 132 or encapsulated.…”
Section: Pathologymentioning
confidence: 99%
“…130 Rates of vascular invasion are significantly lower in tumours that are small, 131 histologically well differentiated 132 or encapsulated. 129 It has also been found that tumours arising in women are more likely to be encapsulated 133 and less likely to show vascular invasion.…”
Section: Pathologymentioning
confidence: 99%
See 1 more Smart Citation